THE INFLUENCE OF BRAND IMAGE AND DIGITAL MARKETING ON REPURCHASE INTENTION OF REEBOK SHOES WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE: (A Survey of Private University Students in Kuningan Regency) - Salsha Billa Azzhara Azzhara; Dikdik Harjadi; Wachjuni Wachjuni; Wely Hadi Gunawan (Universitas Kuningan, 2025)
This study aimed to examine the influence of brand image and digital marketing on the repurchase intention of Reebok shoes, mediated by customer satisfaction. The research used a quantitative method with a survey approach involving 140 private university students in Kuningan Regency who use Reebok shoes. Data analysis was conducted using the Partial Least Square (PLS) method with SmartPLS software. The results of the study indicate that: (1) brand image has a positive and significant influence on customer satisfaction. (2) digital marketing has a positive and significant influence on customer satisfaction. (3) brand image has a positive and significant influence on repurchase intention. (4) digital marketing has no influence on repurchase intention. (5) customer satisfaction also has a positive and significant influence on repurchase intention. (6) brand image has a significant influence on repurchase intention through customer satisfaction. (7) digital marketing has a significant influence on repurchase intention through customer satisfaction.